(3GdESYGO HTQM GdEQTGOs - (3ceGd GdOjf eMeO Hf eMeO Hf CHi HcQ Hf Ydj Hf CHi TQja GdebOSi GdTGaYjs; (3TQa GdOjf ESeGYjd Hf CHj HcQ Hf YHO Gddg Hf EHQGgje GdebQj GdTQLj GdMSjfj, GdTGhQj GdRHjOj Gdjefj,J (B837 (3g` s
(3ChdgG (B:s
(3HGH GdHjY hgh dZI ebGHd TF HTF , hjWdb TQYkG deYfjjf , CMOgeG ebGHd eYfi GdTQGA , hgh HgPG GdeYfi Jedjc jejf Ch efaYI s
(3BNQgG (B:s
(3BNQg fGbU , hBNQ GdehLhO efg ai ChGFd HGH GdaQGFV (B" (3aEf cGf JGdakG JYdb Mbg HGdeZUhH hbOe Hg fU Ydjg ai GdCe, hMcGg ai GdeWdH hefg GdJYdb s
(3eJf GdEQTGO HGdMeQIs
(3Ydi GdfSNI Jedc UGMH GdecJHI YeQ Hf CMeO YehOiGdeJhai SfI (B947(3g`s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YeQ Hf CMeO GdYehOi GdYGeg MQjVg s
Keywords: (3Gdabg GdTGaYjs